Akute bilaterale Visusminderung mit Zentralskotom bei einem 11-jährigen Jungen - Marx, Stefanie; Ach, Thomas; Schaal, Karen; Dithmar, Stefan (Der Ophthalmologe, 2012)
This article presents a case of acute bilateral impaired vision and central scotoma in an 11-year-old boy. Looking directly into a laser beam of a laser pointer for only a few seconds can cause retinal damage in the form of lesions of the retinal pigment epithelium and the photoreceptor layer, up to retinal hemorrhage. Patients often complain about impaired vision and a central scotoma of the affected eye.